Penerapan Model Pembelajaran Role Playing (Bermain Peran) dalam Membentuk Karakter Mahasiswa sebagai Calon Pendidik di Universitas Patompo - Bungatang Bunga; Khaerati; Israwati Akib (Universitas Muhammadiyah Sorong, 2022)
The Role-Playing learning model is a learning model which can assist the students to understand, think, and act alone by acting out the behavior of others in real life in the form of group discussion activities. This study aims to determine the influence of role-playing learning models in building students’ character in overcoming moral degradation in the world of education. The results of this study are expected to build the character of students to be better in living in society. This research was conducted with a qualitative approach and the research design was Class Action Research. The research was carried out with 2 cycles by following the Role-Playing learning model. The population of this research was all students of FKIP, Universitas Patompo, while the sample of this research was class 1B students of Economic Education of FKIP, Universitas Patompo with the total number of students were 40. This research applied qualitative and quantitative data. Qualitative data was obtained through observation and questionnaire techniques, while quantitative data was obtained through direct tests, namely role-playing in building the students’ character. Qualitative data was analyzed through three stages, namely data reduction, data display, and conclusions, while quantitative data was analyzed by using descriptive statistics. The result of the research shows that there is an increase in the average score of each aspect assessed in character learning by applying the role-playing learning model in cycle I and cycle II, it can be concluded that the Role-Playing learning model can be an interesting learning method and can overcome the moral degradation of students of Economics Education at FKIP Universitas Patompo. Keywords: Character-Building, Role-Playing